Battery eruption triggered by plated lithium on an anode during thermal runaway after fast charging. (15th January 2022) - Li, Yalun; Gao, Xinlei; Feng, Xuning; Ren, Dongsheng; Li, Yan; Hou, Junxian; Wu, Yu; Du, Jiuyu; Lu, Languang; Ouyang, Minggao
Abstract: Lithium-ion batteries (LIBs) are suffering from severe thermal runaway risks in the use of their whole lifespans. The heat release characteristics of thermal runaway after fast charging have been proven to be highly related to lithium plating, yet whose impacts on the eruption behaviors are rarely investigated. In this study, the changes in the battery eruption temperature during thermal runaway after fast charging are thoroughly analyzed, and the effects of lithium plating on gas production are revealed. Accelerating Rate Calorimetry tests of pouch cells and prismatic cells are performed to investigate the eruption temperature of LIBs charged at different rates, confirming the advanced eruption of thermal runaway on batteries with plated lithium. To reveal the root cause of early eruptions, reactions between plated lithium and electrolytes are characterized by Synchronous Thermogravimetry Analysis and Mass Spectrometry, observing the fierce gas production process. Afterwards, and the gas and solid products of the reaction are further obtained using partially reactive systems in hot-box tests, and their compositions are analyzed. Overall, this study contributes to a more profound understanding of the characteristics of thermal runaway after fast charging, providing valuable insights on the rational design and management for LIB safety. Highlights: Battery eruption temperature in thermal runaway are decreased after fast charging. The advanced eruption is caused by reaction between plated lithium and electrolyte. The gas and solid products of the reaction are obtained to characterize safety risk.